The Efektivitas Pengawasan Keuangan Negara oleh Badan Pemeriksa Keuangan sebagai Upaya Preventif terhadap Tindak Pidana Korupsi - Habibi, Iskan; Tjandra, W. Riawan (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2026)
Supervision of state finances plays a strategic role in preventing corruption practices that harm the economy and state finances. The Audit Board of Indonesia (BPK), as an institution granted constitutional authority, has the primary task of auditing the management and accountability of state finances, both at the central and regional levels. This article aims to analyze the effectiveness of the oversight conducted by the BPK in preventing corruption and to identify the challenges and obstacles faced, particularly related to resource limitations, follow-up on audit results, and synergy with law enforcement agencies. Through a normative approach by examining constitutional provisions, laws, and legal doctrines, it was found that although the BPK has procedurally carried out its functions of financial, performance, and investigative audits, its effectiveness is still not optimal. One of the main obstacles is the low level of follow-up on audit recommendations, as well as the absence of strict sanctions against parties who do not implement the recommendations. In addition, the inconsistency between BPK's findings and the outcomes of legal proceedings also raises doubts about the consistency of oversight. Therefore, there is a need for institutional strengthening, enhancement of auditor capacity, utilization of modern audit technology, and closer coordination with law enforcement agencies so that the oversight function of the BPK can significantly contribute to preventing corruption and realizing good governance.